Histopatologi Hepar Tikus Dengan Induksi Pakan Tinggi Lemak Setelah Pemberian Biji Mahoni - Agave Chintya Gabriella Sijabat; Sri Isdadiyanto; Agung Janika Sitasiwi (Jurnal Ilmu Pertanian Indonesia, 2024)
High accumulation of lipids in hepatocytes can trigger an increase in the production of radical compounds, leading to fatty liver disease. This condition induces histological changes in the liver, especially in hepatocytes, and affects the surrounding structures. Mahogany seeds have the potential to act as a hypolipidemic agent in treating fatty liver. Mahogany seeds are known to contain phytochemical compounds which act as antioxidants. This study aimed to determine liver histopathology of rats by inducing high-fat diet after giving mahogany seeds ethanol extract which was observed through the percentage of steatosis, hepatocyte diameter, and hepatosomatic index. This study involved thirty male Sprague Dawley rats, divided into 6 groups: P0 (given commercial feed), P1 (given high-fat diet), P2 (given high-fat diet and simvastatin at a dose of 8 mg/200 g BW), P3, P4, and P5 (given high-fat diet and mahogany seeds ethanol extract at a dose of 14, 28, and 56 mg/200 g BW). The results showed that the hepatosomatic index among all treatment groups did not differ significantly; however, the percentage of steatosis and hepatocyte diameter in the groups given mahogany seeds ethanol extract significantly differed from the group given only high-fat feed. Based on these results, it can be concluded that mahogany seed ethanol extract can maintain the histological structure of the liver in male Sprague Dawley rats with fatty liver. Keywords: hepatocyte, hepatosomatic index, high-fat diet, mahogany seeds, steatosis